Firefighters's occupational exposure to PM2.5 and polycyclic aromatic hydrocarbons - Oliveira, Beatriz (2016)
This study collected the personal PM2.5 air fraction in fifteen healthy and no-smoking firefighters during their normal shift inside four Portuguese fire stations. Indoor PM2.5 levels varied between 0.05 to 1.04 µg/m3. Polycyclic Aromatic Hydrocarbons (PAHs) are known for their ubiquity and toxicity, being some of them classified as carcinogenic and possible carcinogens to humans. Firefighters’ personal PM2.5-bound total PAH concentrations ranged between 35.8 to 294 ng/m3 with total carcinogenic PAHs accounting with 12% to the total PAHs. Benzo[a]pyrene, the PAH biomarker of carcinogenicity, was detected in levels ranging from 6.74 × 10-2 to 1.00 ng/m3